Empowering Tech-Savvy Youth Education in Society 5.0: Transforming Learning for the Digital Future - Erni Murniarti; Bintang R. Simbolon; Reza Yuridian Purwoko; Endang Fatmawati; Hariyanto (Global Writing Academica Researching & Publishing, 2023)
Dynamic changes in the digital era demand an educational approach that is responsive to student needs and the demands of an increasingly connected society. Lack of student involvement can be an obstacle to achieving learning goals that are holistic and relevant to technological developments. Therefore, there is an urgency to understand and optimize youth participation in Society 5.0 through innovative education. This research aims to investigate the positive impact of innovative education on youth participation in Society 5.0. Through a descriptive qualitative approach, this research uses data from previous research and studies that are still relevant to the phenomenon being observed. By understanding the role of teachers, innovative learning models, and student skill development, this research is aimed at illustrating how innovative education can increase student engagement and prepare them to face a dynamic future. By analyzing the role of teachers, innovative learning models, and student skills development in the context of Society 5.0, this research finds that innovative education has a significant positive impact on youth participation. This emphasizes the importance of the role of teachers as agents of change in adopting innovative approaches, to create a learning environment that motivates and supports student creativity. The integration of technology, particularly through a project-based approach and the use of virtual reality, has proven effective in increasing student engagement and preparing them to face future challenges.